# Math(please check)

posted by .

1) Differentiate the following:

a) y=(x^3+5x)^6 (x^2+1)^7

(6(x^3+5x^)^5 * 3x^2+5) + (7(x^2+1)^6 *2x) * (x^3+5x)^6

b) y=(x+1)^2 / x^2

(2(x+1)*1) * (x^2) - 2x *(x+1)^2 all over (x^2)^2

Are these correct?

• Math(please check) -

(6(x^3+5x^)^5 * 3x^2+5) + (7(x^2+1)^6 *2x) * (x^3+5x)^6
add ( paren
(6(x^3+5x^)^5 * (3x^2+5) + (7(x^2+1)^6 *2x) * (x^3+5x)^6

• Math(please check) -

2x(x+1) all over x^4
2(x+1)/x^3

the first one can be simplified further as well, like take out (x^3+5x)^5 for starters

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### Math- Check over please

A ball is dropped from a height of 3m and bounces on the ground. At the top of each bounce, the ball reaches 60% of it's previous height. Calculate the total distance travelled by the ball when it hits the ground the fifth time. Could …
2. ### trigo help!

1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are constants. 5. differentiate xsin(a/x) where a is constant 6. differentiate sec^3(3x^2+1)
3. ### Math

Can someone please check my answers below for accurateness?
4. ### math

How can the teacher differentiate instruction when teaching number sense or mathematical operations?
5. ### Math(Please check. Thank You)

1) solve:e^x(x^2-4)=0 e^x=0 and then (x+2)(x-2) so x=2, -2 2) differentiate: y=ln(6x^2 - 3x + 1) 1/(6x^2 - 3x + 1) * 12x-3 3) differentiate: y=e^-3x+2 -3 * e^-3x+2 4) evaluate: 2^4-x=8 2^4-x = 2^3 4-x = 3 -x=-1 so x=1 5) differentiate: …
6. ### Calculus

I think I have the correct answers for the following problems. For anyone who has the time I would appreciate it if you could tell me if I am correct/incorrect. Thank you. 1). Differentiate ã(x)sin x = (2xcosx+sinx)/2ã(x) 2). …
7. ### math-check

I have solved the following questions, let me know if they are correct, thanks. 1. Simplify, and write in the base of 3: (9^x . 3^4x)^2 answer: 3^12x 2. Differentiate and simplify a. y= 3x^4 - 4e^x + 8 answer: 4(3x^3 - e^x) b. y= (3 …
8. ### Calculus - please check my work

Differentiate each function a) y = -3x^2 + 5x - 4 b) f(x) = 6/x - 3/(x^2) c) f(x) = (3x^2 - 4x)(x^3 + 1) the answers i got for each was: a) y'= -6x + 5 b) f'(x)= -6/x^2 + 6/x^3 c) f'(x)= 15x^4 + 6x - 16x^3 - 4 please double check and …
9. ### Math (check answer plz)

13. A true-false test has 12 questions. What is the probability of guessing the correct answers to all of the questions?
10. ### algebra help me please

The equation below shows the area of a trapezoid, A, with a height of 9 cm, and one base 35 cm. A = 9 over 2(b + 35) Which of the following formulas correctly solves for the other base, b?

More Similar Questions